The Screening of Antiphospholipid Antibodies in Obstetric Antiphospholipid Syndrome-Like Events: A Regional Perspective - Onder Onen; Fusun Gulizar Varol (Gynecology Obstetrics & Reproductive Medicine)
Objective: Obstetric antiphospholipid antibody syndrome is clinically recognized by adverse obstetric outcomes. To determine which antibody level best corresponds to the risk of these clinical outcomes is difficult. Obstetric antiphospholipid antibody syndrome-like adverse obstetric outcomes with single (n=108) and repeat (n=79) documented antiphospholipid antibody titers were evaluated.